The 30 day MBA in marketing : your fast track guide to business success - Barrow, Colin (London: KoganPage, 2016)
"The 30 Day MBA in Marketing provides a one-stop comprehensive overview of marketing for small business owners, entrepreneurs, or managers who do not have an MBA degree. This updated second edition offers brand new case studies and covers current trends including mobile marketing, social media marketing, and marketing science developments, as well as traditional topics such as buyer behavior, marketing strategy, advertising and promotion, pricing, and marketing and the law"--
"The 30 Day MBA in Marketing provides a complete marketing 'course' spanning twelve disciplinary areas, and including such hot topics as: buyer behaviour, marketing strategy, promotion and advertising, pricing, managing the marketing organization and marketing and the law. Each chapter includes at least one practical real life example to illustrate how marketing concepts apply to business decision making. Learn what they teach you on professional marketing courses and at the world's top Business Schools and why it matters to you; eliminate gaps in your marketing knowledge and take part in business decision making on an equal footing with MBA graduates or your company marketing director. This book includes detailed information on how to find and analyse market data on any business or market anywhere and online appendices that provide an invaluable guide to finding further information and free resources on each topic covered"--
Keywords: Marketing; Master of business administration degree; BUSINESS & ECONOMICS / Skills; BUSINESS & ECONOMICS / Careers / General; STUDY AIDS / Professional; BUSINESS & ECONOMICS / Marketing / General; STUDY AIDS / Graduate School Guides